Changes in plant community and soil ecological indicators in response to Prosopis juliflora and Acacia mearnsii invasion and removal in two biodiversity hotspots in Southern India - Murugan, Rajasekaran; Beggi, Francesca; Prabakaran, Nehru; Maqsood, Shafique; Joergensen, Rainer Georg (Springer, 2020)
Invasion of alien plant species can alter local plant diversity and ecosystem processes closely linked to soil organic carbon (SOC) and nutrient dynamics. Soil ecosystem processes such as microbial respiration and enzyme activity have been poorly explored under alien plant invasion and especially following invasive plant species removal. We studied the impact of Prosopis juliflora and Acacia mearnsii invasion and subsequent removal on local plant community composition and diversity and on soil microbial respiration and enzyme activity in two biodiversity hotspots in Southern India. Removal of Prosopis promoted recolonisation of local vegetation as indicated by a 38% and 28% increase in species richness and ground vegetation cover, respectively, compared to an unremoved site. Prosopis and Acacia removal led to a significant reduction in soil microbial biomass C (MBC), respiration, dehydrogenase and urease activity due to increased microbial respiration and N mineralisation rate. Higher metabolic quotients qCO2 in soil at Prosopis and Acacia removed sites indicate that MBC pools declined at a faster rate than SOC, resulting decreased MBC/SOC ratios compared to their respective removed sites. Natural and undisturbed ecosystems maintain more SOC through increased belowground and aboveground C input in the soil, resulting in a higher MBC content per unit SOC. Our results indicate that the interaction between above- and below-ground communities is a critical factor determining the structure and dynamics of local plant communities, especially in ecosystems affected by plant invasions.